PENGARUH TIPE INDUSTRI, MEDIA EXPOSURE, PROFITABILITAS DAN STAKEHOLDER TERHADAP CARBON EMISSION DISCLOSURE (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA PADA TAHUN 2013-2017) - Desy aria sandi; Dwi Soegiarto; Dianing Ratna Wijayani (Universitas Muria Kudus, 2021)
This research was motivated by the low number of industries in Indonesia reporting carbon emission information.Disclosure of carbon emissions is an issue related to the impact of climate change on the sustainability of the organization. This study aims to examine the effect of target industry types, media exposure, profitability, and regulators on carbon emissions' disclosures (CED). Determination of this sample using purposive sampling method with a sample size of 60 companies in the period 2013-2017.This study uses multiple linear regression analysis techniques.The results of this study indicate that industry type, and profitability have a positive and significant effect on CED, while media exposure, and regulator, have no significant effect on CED.